Self-assessment of the Qualitative Maturity of the Organization - Wiesław ŁUKASIŃSKI; Anna SZARŁOWICZ POLAND (Communications of International Proceedings, 2021)
Contemporary organizations function in a dynamically changing and complex environment, which means that they have to face various challenges in a short period, time, such as increasing customer expectations or fierce competition. It is possible when they improve the competences necessary to increase the level of qualitative maturity of the organization, understood as the ability to act conditioning the development of the expected value, i.e. meeting the needs and expectations of stakeholders. A qualitatively mature organization is characterized by operational efficiency, increased competitiveness and achievement of lasting success, understood as the ability to develop in the long term. Therefore, it becomes important to obtain information about the current level of qualitative maturity of the organization. The objectives of the work are to define the concept and indicate the meaning of the qualitative maturity of the organization and to present a self-assessment tool that can be used in the process of measuring and shaping it. The achievement of the chosen goals was possible thanks to a literature review, a questionnaire survey among specialists dealing with the organization management process and the application of the developed tool in practice. The conducted research, the obtained results and the proposed concept of measuring and shaping the qualitative maturity of an organization, in addition to practical application, may inspire people seeking to develop tools aimed at increasing the effectiveness of pro-quality organization management.
Keywords: Organization; Qualitative Maturity Of The Organization; Self-Assessment